Optimising Nutrients for Papaya as an Intercrop in Juvenile Coconut Plantations - Nihad, K.; Abdul Haris, A.; Neenu, S.; Bhat, Ravi (Journal of Plantation Crops, 2026)
Coconut cultivation, predominant in coastal India, faces a prolonged juvenile phase of 3–5 years during which economic returns are minimal. Intercropping with short-duration fruit crops like papaya (Carica papaya L.) offers a sustainable solution for income generation during this period. A field experiment was conducted at ICAR-CPCRI, Regional Station, Kayamkulam, to evaluate nutrient management strategies for papaya under a juvenile coconut ecosystem using organic residue recycling. Three papaya varieties—Taiwan 786, Co 8, and Arka Prabhat—were planted in a single row in between coconut palms, under four nutrient treatments at bimonthly intervals using different organic amendments; coconut leaf vermicompost (CLVC), rock phosphate, neem cake, poultry litter, and green manure. The experiment was laid out in factorial randomised block design with four replications. Results indicated that the treatment comprising 2 kg CLVC, 200 g rock phosphate, and 100 g sulphate of potash recorded enhanced growth and yield parameters plant height (174.4 cm), length of leaf midrib (78.88 cm),total dry matter production (2.9 kg plant-1), fruit weight (1.33 kg), and productivity (20.42 fruits plant-1) .This treatment also recorded higher chlorophyll content (1.11 %) and reduced stomatal resistance (1.02 mmol m−2 s−1 ) suggesting improved photosynthetic efficiency. Elevated nitrogen and potassium levels in plant tissues further corroborated the superior performance of this nutrient regime. The study highlights the potential of organic nutrient management in optimizing papaya productivity within coconut-based intercropping systems.